A theoretical framework of sustainability in air transportation planning and future prospects of airport infrastructure upgrading : a case study of Kuala Lumpur International Airport 2 (KLIA 2) - Sahrir, Syazwani; Bachok, Syahriah; Mohamed Osman, Mariana (2012)
Air transportation has become the fastest growing mode of transportation in adapting with the transportation facilities and services provided. The developments of air transportation have surrounded with the introduction of much larger transport aircraft and rising airport infrastructure upgrading nowadays. Due to the increasing importance of enlargements in airport facility, this has become a concern for policy makers and academics. Although the time value and greatest cost efficiency are obtained from the airport facilities, there are negative externalities produced by airport developments. Due to the increasing importance of enlargements in airport capacity, it should also regard as the management of the environmental impact on surrounding areas. Literature has found that airport operations may produce various regulated pollutants, including volatile organic compounds (VOCs), carbon monoxide (CO), and particulate matter (PM) (Luther, 2007).This paper aims at identifying the sustainability in air transportation planning and future prospects of airport infrastructure upgrading; using the KLIA 2 as a case study. At most airports, the major environmental concerns embrace local air quality, noise, sustainability and recycling along with habitat and wildlife management. Issues relating to the sustainability of specific industrial sectors such as aviation are relatively under researched. Procedures and technologies for environmental protection, environmental efficiency and impact mitigation receive a considerable degree of attention from industry, government and academia alike has to be increased. Even though the airport expansion is very important to cater the demand, however, there are some policies and strategies that need to be considered to balance the need and the future. Conventionally, the planning of airport infrastructure upgrading has only focused on elements surrounded by the airport; such as supply and demand forecasts and other aeronautical and engineering. But the recent airport framework presents new situations that cannot be solved by traditional methods since new and external variables are intrinsic to the decision-making process (Graham and Guyer, 1999).The study will focus on the environmental impacts of the KLIA 2 constructions which are ongoing. However, this paper highlight the literature background on impact of airport expansion on air pollution and noise issues to the environment as well as to the community.